Effect of Rice Distiller and Stylo on Growth Of Muscovy duck - NAOYENG, Khamkeo; Vhar, Ku (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This study aimed to investigate the effectiveness of using distiller and Stylo on growth of native duck and economic returns of raising native duck. The experiment took three monthsand data collection was taken for 49 days. There were 9 pens, each pen covered by Black net, zinc roof, and round cover by plastic . Each pen contained three native ducks with water and food trays. Muscovy duck were raised inside the pen with 90cm width, 90cm length, and 90cm high. Muscovy duck were fed 2 times a day (7:00 Am and 16:00 Pm). Weight of feed, remained feed after feeding was recorded everyday. Animal weight was recorded every 7 days. The result revealed that T2 obtained highest mean feed intake (g/duck/day) by 560.05g, folowed by T1 (537.77g). Whereas, the lowest feed intake was significantly found in T3= 494.68g (P<0.05). ADG (g/duck/day) was found to be highest in T1= 37.6g, followed by T2 = 35.87g. However, T3 obtained lowest ADG (35.6g). In addition, FCR of native ducks was significantly different (P<0.05). T1 showed the highest value (4.45), followed by T3 (4.91). Whereas, the lowest FCR found in T2 (5.25). Economic return of raising native ducks were different in each treatment. T3 obtained 380,375LAK, followed by T2 = 344,375. The lowest economic outcome was T1 =222,375 LAK.